MAMMALS OF SOUTHWESTERN BUNGO RANGE - Faisal Ali, Anwarali Khan; Syamzuraini, Zolkapley; Muhd Amsyari, Morni; Julius William, Dee; Mohammad Zahid, Zainal Abidin; Praveena, Rajasegaran; Yuvarajan, A/L Manivannan; Qhairil Shyamri, Rosli; Norfarhana, Mazlan; Roberta Chaya Tawie, Tingga; Mohd Ridwan, Abd Rahman (UNIMAS Publisher, 2023)
The Bungo Range NP covers an area of 8096 hectares that consist mainly of limestone forest with some small areas of peat swamp forest and mixed dipterocarp forest (Sarawak Forestry Corporation, 2020). The presence of two major limestone caves nearby, Wind Cave and Fairy Cave Nature Reserve indicate that the geological structures, forest, and mountains in the district of Bau are unique. While the area is expected to host a large variety of flora and fauna due to its diverse surrounding ecosystems, it is one of the least explored national parks in Sarawak.